Object Recognition Using Keras with Backend Tensor Flow - Bandi, Raswitha; Amudhavel, J (International Journal of Engineering and Technology, 2018)
Now a dayâ€™s Machine Learning Plays an important role in computer vision, object recognition and image classification. Recognizing objects in images is an interesting thing, this recognization can be done easily by human beings but the computer cannot. The Problem with traditional neural networks is object recognition. So, to avoid difficulties in recognition of objects in images the deep neural networks especially Tensor flow under Keras Library is used and it will improve the Accuracy while recognizing objects. In this paper we present object recognition using Keras Library with backend Tensor flow.Â